2010
DOI: 10.1159/000319473
|View full text |Cite
|
Sign up to set email alerts
|

Research Ethics in the Era of Personalized Medicine: Updating Science’s Contract with Society

Abstract: With the completed sequence of the human genome has come the prospect of substantially improving the quality of life for millions through personalized medicine approaches. Still, any advances in this direction require research involving human subjects. For decades science and ethics have enjoyed an allegiance reflected in a common set of ethical principles and procedures guiding the conduct of research with human subjects. Some of these principles emphasize avoiding harm over maximizing benefit. In this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…For example, the deliberants indicated that biobanks should be used for the common good and that this should prevail over the research interests of the initiators and users of the biobank. Meslin and Cho [52] present a similar position in arguing for a new social contract between genetic researchers and the public. Collectively, the similarities undoubtedly heightened the extent to which the deliberants’ recommendations became evident in the policy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the deliberants indicated that biobanks should be used for the common good and that this should prevail over the research interests of the initiators and users of the biobank. Meslin and Cho [52] present a similar position in arguing for a new social contract between genetic researchers and the public. Collectively, the similarities undoubtedly heightened the extent to which the deliberants’ recommendations became evident in the policy.…”
Section: Discussionmentioning
confidence: 99%
“…In short, low levels of funding have adverse consequences for society in general as biomedical or genomic research yields prosperity and other economic benefits by creating jobs and valuable products and methods [3,27]. …”
Section: Research Ethics 20: New Perspectives On Norms Values and mentioning
confidence: 99%
“…The scientific process is embedded in a complex network with different stakeholders, which need to be more systematically addressed. Meslin and Cho [3] analysed the existing “common set of ethical principles” in research ethics and proposed a reframing of the “social contract” between science and society, highlighting the need to put focus on the broader context of research. With this paper, we will extend the existing body of knowledge assessing the development or evolution of research ethics by highlighting the current challenges to scientific integrity.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It is widely recognized that physicians entering medical practice in the 21st century will require more than a basic understanding of human genetics.…”
Section: Importance Of Genetic and Genomic Fluency For The Practicingmentioning
confidence: 99%
“…[1][2][3][4] Concomitant with the advancement of genetic knowledge and technologies is the emergence of ethical and public policy concerns related to their application to medical practice. 5,6 It is widely recognized that physicians entering medical practice in the 21st century will require more than a basic understanding of human genetics.…”
Section: Importance Of Genetic and Genomic Fluency For The Practicingmentioning
confidence: 99%